Crop residue markets in West Africa provide short term gains to farmers - Abdoulaye, Tahirou (International Livestock Research Institute, 2009)
Reporting on his research project at the December 2009 SLP meeting in Addis Ababa, Tahirou Abdoulaye (IITA) explains: "What is clearly coming out is the role of market where feed markets, crop residue markets, are emerging ... and the immediate benefit is for farmers to give more of their crop residues to their livestock because the other gains, in terms of soil fertility, tend to be more long term oriented, and farmers tend to focus more on the short term gains."